Continuity of maternal healthcare services utilisation in Indonesia: analysis of determinants from the Indonesia Demographic and Health Survey. Issue 4 (22nd December 2021) - Andriani, Helen; Rachmadani, Salma Dhiya; Natasha, Valencia; Saptari, Adila
Abstract : Objective: WHO recommends that every pregnant woman and newborn receive quality care throughout the pregnancy, delivery and postnatal periods. However, Maternal Mortality Ratio in Indonesia for 2015 reached 305 per 100 000 live births, which exceeds the target of Sustainable Development Goals (<70 per 100 000 live births). Receiving at least four times antenatal care (ANC4+) and skilled birth attendant (SBA) during childbirth is crucial for preventing maternal and neonatal deaths. The study aims to assess the determinants of ANC4 +and SBA independently, evaluate the distribution of utilisation of ANC4 + and SBA services, and further investigate the associations of two levels of continuity of services utilisation in Indonesia Design: Data from the Indonesia Demographic and Health Survey, a cross-sectional and large-scale national survey conducted in 2017 were used. Setting: This study was set in Indonesia. Participants: The study involved ever-married women of reproductive age (15–49 years) and had given birth in the last 5 years prior to the survey (n=15 288). The dependent variables are the use of ANC4 + and SBA. Individual, family and community factors, such as age, age at first birth, level of education, employment status, parity, autonomy in healthcare decision-making, level of education, employment status of spouses, household income, mass media consumption residence and distance from health facilities were also measured. Results: Results showed that 11 632 (76.1%) women received ANC4 + and SBA during childbirth. Multivariate analysis revealed that age, age at first birth, and parity have a statistically significant association with continuity of services utilisation. The odds of using continuity of services were higher among women older than 34 years (adjusted OR (aOR) 1.54; 95% CI 1.31 to 1.80) compared with women aged 15–24 years. Women with a favourable distance from health facilities were more likely to receive continuity of services utilisation (aOR 1.39; 95% CI 1.24 to 1.57). Conclusions: The continuity of services utilisation is associated with age, reproductive status, family influence and accessibility-related factors. Findings demonstrated the importance of enhancing early reproductive health education for men and women. The health system reinforcement, community empowerment and multisectoral engagement enhance accessibility to health facilities, reduce financial and geographical barriers, and produce strong quality care.